2020
DOI: 10.1101/2020.11.03.365502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Baculovirus actin-rearrangement-inducing factor ARIF-1 induces the formation of dynamic clusters of invadosome-like structures

Abstract: The baculovirus Autographa californica multiple nucleopolyhedrovirus (AcMNPV), a pathogen of lepidopteran insects, has a striking dependence on the host cell actin cytoskeleton during infection. During the delayed-early stage of AcMNPV infection, the virus was shown to induce the accumulation of filamentous actin at the cortex of infected cells. However, the dynamics and molecular mechanism of cortical actin assembly remained unknown. Using live cell imaging, we show that AcMNPV induces the formation of dynami… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Arif-1 is expressed at the early stage of baculovirus infection and co-localizes with F-actin at the plasma membrane until late gene expression. It has been suggested that ARIF-1 induces the formation of invadosome-like structures, leading to the formation of organized structures to enable systemic viral spread [ 40 ]. The fast and early translocation of the nucleocapsids to the nucleus is critical for baculovirus replication.…”
Section: Baculoviruses Hijack the Host Cells Cytoskeleton Actin To Replicate And Spread The Infectionmentioning
confidence: 99%
“…Arif-1 is expressed at the early stage of baculovirus infection and co-localizes with F-actin at the plasma membrane until late gene expression. It has been suggested that ARIF-1 induces the formation of invadosome-like structures, leading to the formation of organized structures to enable systemic viral spread [ 40 ]. The fast and early translocation of the nucleocapsids to the nucleus is critical for baculovirus replication.…”
Section: Baculoviruses Hijack the Host Cells Cytoskeleton Actin To Replicate And Spread The Infectionmentioning
confidence: 99%